2007
DOI: 10.1007/s10517-007-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of high-density lipoproteins in patients with arterial hypertension in combination with other components of metabolic syndrome

Abstract: Parameters of HDL (concentrations of cholesterol, apoprotein A1, and phospholipids and phospholipid composition) determining their functional properties were studied in patients with arterial hypertension in combination with other components of metabolic syndrome (abdominal obesity, hyperlipidemia, and impaired glucose tolerance). Patients with isolated arterial hypertension did not differ from the control group by the concentration of apoprotein A1 and HDL cholesterol, but had lower content of HDL phospholipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
1
13
0
Order By: Relevance
“…Similarly, HDL from patients with malaria ( 117 ) and uremic patients on hemodialysis ( 91 ) displays elevated content of triglyceride, whereas HDL from patients with psoriasis is depleted in cholesteryl ester ( 92 ). Cytokine-induced increase in the activity of CETP paralleled by decreases in the activities of hepatic lipase, LPL, and LCAT can underlie hypertriglyceridemia, altered phospholipid composition characterized by elevated content of LPC and PE and diminished content of PC ( 90 ). Consistent with these data, HDL obtained from patients on maintenance hemodialysis contained reduced amounts of phospholipid and elevated amounts of lysophospholipid ( 91 ).…”
Section: Cholesteryl Esters and Triglyceridesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, HDL from patients with malaria ( 117 ) and uremic patients on hemodialysis ( 91 ) displays elevated content of triglyceride, whereas HDL from patients with psoriasis is depleted in cholesteryl ester ( 92 ). Cytokine-induced increase in the activity of CETP paralleled by decreases in the activities of hepatic lipase, LPL, and LCAT can underlie hypertriglyceridemia, altered phospholipid composition characterized by elevated content of LPC and PE and diminished content of PC ( 90 ). Consistent with these data, HDL obtained from patients on maintenance hemodialysis contained reduced amounts of phospholipid and elevated amounts of lysophospholipid ( 91 ).…”
Section: Cholesteryl Esters and Triglyceridesmentioning
confidence: 99%
“…On the other hand, HDL SM is elevated in patients with isolated arterial hypertension ( 90 ) and with psoriasis ( 92 ). Interestingly, SM enrichment in HDL may selectively inhibit generation of specifi c molecular species of cholesteryl esters catalyzed by LCAT, altering the plasma profi le of cholesteryl esters ( 106 ).…”
Section: Sphingolipidsmentioning
confidence: 99%
“…6 It has been reported that the HDL concentration of patients with hypertension does not differ from that of healthy controls, but the phospholipid compositions of HDL are altered, which may impair the functional capacity of HDL in inducing cholesterol efflux. 7 On the cellular aspects of cholesterol efflux, no studies regarding the expression of the three important transporters/receptor of ABCA1, ABCG1 and SR-BI, and their functional effects of cholesterol efflux in hypertensive conditions, have been carried out. Therefore, the aims of this study were to investigate whether the expression of ABCA1, ABCG1 and SR-BI in peripheral blood monocytes was changed in hypertensive patients, as well as its alteration on anti-hypertensive therapy, and to determine whether these alterations might affect cholesterol efflux from monocyte-derived macrophages ex vivo.…”
Section: Introductionmentioning
confidence: 99%
“…An increased HDL phospholipid concentration has been shown to be a valuable index in patients with multiple myeloma responding to therapy [174] or after periodontal treatment, as HDL phospholipids and the SM/PC ratio also increased in patients with periodontitis [175]. Higher HDL SM was observed in hypertensive patients [176]. …”
Section: Factors Influencing Hdl-smmentioning
confidence: 99%